Migration and Health in Asia - Jatrana, Santosh; Toyota, Mika; Yeoh, Brenda S. A. (Routledge Research in Population and Migration, 2006)
The processes of migration and health are inextricably linked in complex ways, with migration impacting on the mental and physical health of individuals and communities. Health itself can be a motivation for moving or a reason for staying, and migration can have implications on the health of those who move, those who are left behind, and the communities that receive migrants. This volume brings together some of the increasing number of researchers who are studying health and migration in Asia - a continent which is a major exporter and importer of human resources. Using both quantitative and qualitative approaches, the essays included in this work investigate the interdisciplinary issues of health and health-related behaviours in the field of migration. Comprehensive and scholarly, Migration and Health in Asia also covers major themes such as the pandemics of HIV/AIDS and SARS, differential access to health and civil society for migrants, and the health of the populations who are left behind.